1981
DOI: 10.1029/ja086ia07p05682
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of energetic particles in the distant magnetotail

Abstract: The spatial distribution of energetic particles in the distant magnetotail is examined by using identical sets of two complementary energetic particle experiments aboard the IMP 7 and 8 spacecraft. The combined IMP 7 and 8 data set provides nearly 10 years of satellite observation. The quantitative distributions of energetic electrons in two energy ranges (30 keV ≤Ee ≤100 keV, 220 keV ≤Ee ≤2.5 MeV) and energetic protons (50 keV ≤Ep ≤220 keV, 290 keV ≤Ep ≤500 keV) are presented in terms of occurrence frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 25 publications
9
38
0
Order By: Relevance
“…Similar results were also been reported by e.g., Meng et al (1981) and Sarafopoulos et al (2001), but at different radial distances.…”
Section: Local Time Dependencesupporting
confidence: 80%
See 2 more Smart Citations
“…Similar results were also been reported by e.g., Meng et al (1981) and Sarafopoulos et al (2001), but at different radial distances.…”
Section: Local Time Dependencesupporting
confidence: 80%
“…One should then observe higher fluxes of the energetic part of the spectra near the dusk side. This argument was also mentioned byÅsnes et al (2008) (though reversed dawn-dusk asymmetry since they discussed electrons), and also by Meng et al (1981) and Sarafopoulos et al (2001). However, we note that the geomagnetic conditions, reflected by the Dst index, is more disturbed during the dusk traversals (average Dst is −35 nT, versus −8 nT for the dawn side), so this apparent effect does not seem to be solely a local time dependence, but also an effect of different average geomagnetic activity for the two sides.…”
Section: Local Time Dependencementioning
confidence: 55%
See 1 more Smart Citation
“…They occur especially in the Earth's magnetotail in the anti-Sun direction, but also in the magnetosheath which extends to ±∼30 • from the anti-Sun direction, and around the bow shock (to ±∼45 • from anti-Sun); see, e.g., Sarris et al (1976), Baker & Stone (1978), Meng et al (1981). They arise during geomagnetic activity.…”
Section: A2 Particle Event or Not?mentioning
confidence: 99%
“…For example, statistics collected by IMP-8 spacecraft clearly showed that the maximum of fluxes is observed at the dusk flank of the magnetosphere (Meng et al, 1981), where ions drift due to the quasi-stationary gradient drift.…”
Section: A V Artemyev Et Al: High-energy Ion Spectra In the Magnetmentioning
confidence: 99%